2012
DOI: 10.1167/iovs.12-10390
|View full text |Cite
|
Sign up to set email alerts
|

Does Partial Occlusion Promote Normal Binocular Function?

Abstract: PURPOSE. There is growing evidence that abnormal binocular interactions play a key role in the amblyopia syndrome and represent a viable target for treatment interventions. In this context the use of partial occlusion using optical devices such as Bangerter filters as an alternative to complete occlusion is of particular interest. The aims of this study were to understand why Bangerter filters do not result in improved binocular outcomes compared to complete occlusion, and to compare the effects of Bangerter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 44 publications
2
43
0
2
Order By: Relevance
“…Results are shown for different subjects, the denser the filter in front of one eye, the more the balance shifts in favour of the unfiltered eye. Lens blur and Bangerter filters have similar effects . Similarly, in amblyopia where there is an initial imbalance of the inputs of the two eyes due to suppression, lens blur, neutral density filters or Bangerter filters could potentially be used in front of the sighted eye to reduce suppression and re‐balance the inputs of the two eyes .…”
Section: Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are shown for different subjects, the denser the filter in front of one eye, the more the balance shifts in favour of the unfiltered eye. Lens blur and Bangerter filters have similar effects . Similarly, in amblyopia where there is an initial imbalance of the inputs of the two eyes due to suppression, lens blur, neutral density filters or Bangerter filters could potentially be used in front of the sighted eye to reduce suppression and re‐balance the inputs of the two eyes .…”
Section: Suppressionmentioning
confidence: 99%
“…stereopsis). Both neutral density filters and Bangerter filters are less than ideal choices when it comes to stereoscopic function . The way in which they affect the signal emanating from the sighted eye turns out to be particularly detrimental for stereopsis.…”
Section: Suppressionmentioning
confidence: 99%
“…measured using a tumbling E version of the Bailey-Lovie logMAR chart at a standard luminance of 200 cd/m 2 . 49 Best refractive correction was determined by subjective refraction and, if necessary, a trial frame correction was used during testing for both groups. Binocular vision was assessed using the Worth-4-Dot test, 50 the stereo acuity test (Randot Preschool Test; Stereo Optical Co., Inc., Chicago, IL, USA) and the cover/ uncover test was used to ensure the absence of strabismus.…”
Section: Comprehensive Eye Examinationsmentioning
confidence: 99%
“…One of the methods used for the treatment of amblyopia is optical correction followed by occlusion of the eye with better visual acuity to enable the weaker eye to develop 2 . Research on the effects of occlusion has shown that secondary deprivation effects may arise from fixation of the eye and that the occlusion time should not be longer than 6 hours 3 . This trend has also been observed in the ophthalmic community in Brazil, although there is a lack of national clinical evidence 4 .…”
Section: Introductionmentioning
confidence: 99%